Different alkaline earth metals doped Sm0.5A0.5Fe0.9Ni0.1O3-δ (A=Ca, Sr and Ba) for symmetric solid oxide fuel cells. (29th March 2023) - Wang, Jiajia; Chen, Zhengpeng; Li, Mingfei; Rao, Mumin; Li, Ruoyu; Ou, Xuemei; Tian, Yunfeng; Jin, Fangjun; Shen, Chengjin; Ling, Yihan
Abstract: Symmetric solid oxide fuel cells have gained increasingly attention due to their characteristics of simple fabrication and low cost. Due to the same anode and cathode used, the oxygen reduction reaction (ORR) and hydrogen oxidation reaction (HOR) of the electrodes are very demanding. In this work, Sm0.5 × 0.5 Fe0.9 Ni0.1 O3-δ (X = Ca, Sr, Ba, SCFN, SSFN, SBFN) were synthesized, and the physico-chemical properties of three materials and their electrochemical performance as electrodes were systematically studied. They all maintain stable phase structures under oxidizing and reducing atmospheres below 750 °C. X-ray photoelectron spectroscopy (XPS) results showed that metal nanoparticles was exsolved and oxygen vacancies were increased after the treatment in reducing atmosphere at 750 °C. For electrochemical performance test, the peak power densities of symmetrical cells with SCFN-GDC, SSFN-GDC and SBFN-GDC electrodes can reach 26.7, 186.78, and 138.8 mWcm −2 at 750 °C, respectively. Moreover, SSFN-GDC cell showed better long-term stability than the other two. Highlights: Different alkaline earth metals doped SXFN (X = Ca, Sr, Ba) were synthesized. SXFN maintains stable phase structures in redox atmospheres below 750 °C. Fe–Ni metal nanoparticles was exsolved and oxygen vacancies were increased after reduction. SSFN-GDC cell showed better long-term stability than the other two.